The Study Skills Handbook - Cottrell, Stella (Basingstoke : Palgrave Macmillan, 2003)
This is a no-nonsense, practical guide to help students maximise their potential during their time at university. It is packed with sensible suggestions, self-check tables and illustrations, and is printed in blue ink to aid dyslexics.
Previous ed.: Basingstoke: Macmillan, 1999.
Includes bibliographical references (p. 291-293) and index.
Keywords: Study skills; Education